Luquillo Experimental Forest: Catchment science in the montane tropics. Issue 4 (23rd April 2021) - McDowell, William H.; Leon, Miguel C.; Shattuck, Michelle D.; Potter, Jody D.; Heartsill‐Scalley, Tamara; González, Grizelle; Shanley, James B.; Wymore, Adam S.
Abstract: Catchments in the Luquillo Experimental Forest (LEF) of Puerto Rico are warm, wet and tropical with steep elevational relief creating gradients in temperature and rainfall. Long‐term objectives of research at the site are to understand how changing climate and disturbance regimes alter hydrological and biogeochemical processes in the montane tropics and to provide information critical for managing and conserving tropical forest ecosystems globally. Measurements of hydrology and meteorology span decades, and currently include temperature, humidity, precipitation, cloud base level, throughfall, groundwater table elevation and stream discharge. The chemistry of rain, throughfall, and streams is measured weekly and lysimeters and wells are sampled monthly to quarterly. Multiple data sets document the effects of major hurricanes including Hugo (1989), Georges (1998) and Maria (2017) on vegetation, biota and catchment biogeochemistry and provide some of the longest available records of biogeochemical fluxes in tropical forests. Here we present an overview of the findings and the data sets that have been generated from the LEF, highlighting their importance for understanding montane tropical watersheds in the context of disturbance and global environmental change. Abstract : Long‐term studies in montane catchments of Puerto Rico provide important insights into biogeochemical cycles and nutrient export from tropical landscapes